Implementation Evaluation of Performance-Based Budgeting in the Public Service (Studies in the Faculty of "X" University "Y") - Mursitawati, Kurnia; Zaky, Achmad (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determineÂ  the Implementation of Performance-Based Budgeting in the Public Service Agency, as an object of research is of Faculty of "X" University "Y". This study uses qualitative research with a descriptive case study approach. This study uses only the primary data because the techniques used in the collection of data by means of interviews and observations to participate so that researchers directly involved in the activities of the research object. The results showed that the object of research and regulatory administration has implemented a performance-based budget in accordance with the legislation in particular PMK No. 44 / PMK.05 / 2009, which requires BLU preparing budget documents to produce a Business Plan and Budget, but in the preparation of the implementation of the RBA is still some shortcomings, such as not counting achievement of performance, budgetary implementation schedule that does not comply with the planning , the lack of charging indicators and unit costs, lack of socialization in the budget that has been validated and incomplete TOR. Keywords: Performance-Based Budgeting, Public Service Agency, Business Plans and Budget.